Interdependence between agents in multi agent systems - Lau, Pik Lik Billy (Curtin University, 2014)
Interdependence relationships have defined the foundation of cooperation between agents but limited by existing protocols. As a consequence, the idle agents are not able to join and benefit through it. First, the inter-relationship has been studied and certified for the purpose of securing mutual gains. Next, the join coalition mechanism is proposed to help idle agents to join existing macroscopic and microscopic coalitions which are based on the goals compatibilities, budget and trust